Potential energy savings benefits and limitations of radiative cooling coatings for U.S. residential buildings. (15th December 2022) - Wijesuriya, Sajith; Kishore, Ravi Anant; Bianchi, Marcus V.A.; Booten, Chuck
Abstract: Radiative coatings are a promising strategy to implement passive cooling that provides an eco-friendly pathway to achieve energy efficiency in buildings. This study investigates the benefits and limitations of implementing radiative coatings on the building envelope, particularly the roof, of residential buildings in the United States. The analysis compares the performance of an ideal radiative coating with broadband surface properties to a realistic radiative coating with diffuse and semitransparent properties. To enhance the net energy efficiency of buildings, we carried out a comprehensive parametric analysis comprising key radiation surface properties to maximize cooling energy savings while minimizing heating energy penalties. A countrywide assessment for 68 locations across the United States showed that net energy savings are a strong function of the climatic and atmospheric conditions. Broadly, southern locations showed high overall energy savings whereas northern locations exhibited high overall energy penalties. Locations in International Energy Conservation Code (IECC) climate zones 1A, 2A, and 2B showed a net annual energy savings above 5%, whereas locations in IECC climate zones 5B, 6B, and 7 showed a net annual energy penalty greater than 3%. The hot and dry climate of Phoenix, Arizona, showed the highest overall energy savings of 426 kWh (6.2%). Additionally, the mathematical correlation reveals that the net energy savings of a location is positive only when its average cooling degree days is greater than 5.5 or its average heating degree days is less than 10. Highlights: Study investigates energy savings potential of ideal and real diffuse cool coatings for buildings. Impact of radiative coating on the HVAC energy use in 68 US locations is examined. Countrywide assessment shows energy saving as a function of weather and degree days. Energy savings are positive when average cooling degree days is greater than 5.5 Hot and dry climates such as Phoenix, AZ shows highest overall electricity savings of 426 kWh (6.2%).